Characteristics of Salted Catfish (Pangasius hypophthalmus) with the Addition of Green Tea and Lemongrass - Mardalisa Mardalisa; Alqoriffah Hasanah; Mutia Dhiya Amani; Bella Permata Azzahara (Jurnal Perikanan dan Kelautan, 2022)
This study aims to determine the characteristics of salted catfish after the addition of green tea and lemongrass. This research method used a randomized block design (RAK) with one treatment factor and was carried out with 3 repetitions. The treatments used were the addition of 1% green tea and 0,15% lemongrass. The results showed that the treatment had no significant effect on the yield value, water content, ash content, lipid content and protein content of the salted catfish produced. The results of sensory analysis showed that the treatment had a significant effect on appearance, while for aroma, taste and texture it had no significant effect. The best product is with the addition of 0,15% lemongrass which produces a yield value of 57,25%, water content 2.21%, ash content 24,42%, lipid content 29,53%, and protein content 42,96%. Sensory analysis scores for appearance were 7,33 (whole, clean, lusterless), aroma 6,54 (neutral, little additional odor), taste 6,62 (good, species specific, little taste addition), and texture 6,93 (dense, no brittle).